UV-C Radiation as a Factor Reducing Microbiological Contamination of Fish Meal - Krzysztof Skowron; Justyna Bauza-Kaszewska; Zbigniew Dobrzański; Zbigniew Paluszak; Karolina Jadwiga Skowron (The Scientific World Journal)
Fish meals, added to feeds as a source of protein, may contain pathogenic bacteria. Therefore, effective methods for their sanitizing, such as UV-C radiation, are needed to minimize the epidemiological risk. The objective of this study was to evaluate the effect of UV-C radiation on the sanitary state of fish meals. The research materials included salmon and cod meals. Samples of the fish meals were inoculated with suspensions of Salmonella, E. coli, enterococci, and C. sporogenes spores and exposed to the following surface UV-C fluencies: 0–400 J·m−2 for bacteria and 0–5000 J·m−2 for spores. For the vegetative forms, the highest theoretical lethal UV-C dose, ranging from 670.99 to 688.36 J·m−2 depending on the meal type, was determined for Salmonella. The lowest UV-C fluency of 363.34–363.95 J·m−2 was needed for the inactivation of Enterococcus spp. Spores were considerably more resistant, and the UV-C doses necessary for inactivation were 159571.1 J·m−2 in salmon meal and 66836.9 J·m−2 in cod meal. The application of UV-C radiation for the sanitization of fish meals proved to be a relatively effective method for vegetative forms of bacteria but was practically ineffective for spores.